SLiCE: Implementation of automation technology and Internet of Things in the greenhouse - Iwan Kurnianto Wibowo; Bayu Sandi Marta; Eko Susanto; Mochamad Mobed Bachtiar; Mochamad Farhan Eka Widarto; Ahmad Hanan Asy-syaf’ie; Rafi Ahmad Romolo (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
SMK Negeri 1 Sidoarjo aims to create an automated hydroponic greenhouse system with IoT technology. Limited knowledge and costs hinder their progress. However, the Audio Video Engineering Department seeks assistance to achieve the program's goals by upgrading their knowledge and skills in automation. The Service Learning in Computer Engineering (SLiCE) program focuses on introducing and implementing automation and IoT technology in greenhouses. The community service project starts with surveys and discussions involving the principal and teachers. It then proceeds to analyze the needs and develop a hydroponic and IoT automation system. Training is provided for students and teachers of SMK Negeri 1 Sidoarjo. The ESP32 microcontroller enables remote monitoring and automatic control of nutrient levels and water pH, ensuring optimal plant growth. The outcome is a real-time hydroponic automation system capable of monitoring pH, nutrient PPM, and controlling nutrient addition through a website. After training, 87.9% of students reported improved comprehension of IoT and its implementation.